An evolutionary trade‐off between parasite virulence and dispersal at experimental invasion fronts. (14th February 2021) - Nørgaard, Louise S.; Zilio, Giacomo; Saade, Camille; Gougat‐Barbera, Claire; Hall, Matthew D.; Fronhofer, Emanuel A.; Kaltz, Oliver
Abstract: Exploitative parasites are predicted to evolve in highly connected populations or in expanding epidemics. However, many parasites rely on host dispersal to reach new populations, potentially causing conflict between local transmission and global spread. We performed experimental range expansions in interconnected microcosms of the protozoan Paramecium caudatum, allowing natural dispersal of hosts infected with the bacterial parasite Holospora undulata . Parasites from range front treatments facilitated host dispersal and were less virulent, but also invested less in horizontal transmission than parasites from range cores. These differences were consistent with parameter estimates derived from an epidemiological model fitted on population‐level time‐series data. Our results illustrate how dispersal selection can have profound consequences for the evolution of parasite life history and virulence. Decrypting the eco‐evolutionary processes that shape parasite 'dispersal syndromes' may be important for the management of spreading epidemics in changing environments, biological invasions or in other spatial non‐equilibrium settings. Abstract : We performed experimental range expansions in an aquatic model system, with natural dispersal of infected hosts. Parasites from the range front treatment were less virulent and interfered less with host dispersal, but also invested less in horizontal transmission than parasites from the range core. Decrypting the eco‐evolutionary processes that shape parasite 'dispersal syndromes' may be important for the management of epidemics in changing environments, biological invasions or in other spatial non‐equilibrium settings.